Development of Website-Based Learning Media Based on Learner Behaviorism - Ali, Nabila Nurhaliza; Rahayu, Diar Veni (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian ini untuk mengembangkan media pembelajaran berbasis web berdasarkan behaviorisme peserta didik SMP dalam mengasah kemampuan numerasi matematis, serta menguji kelayakan media pembelajaran. Menggunakan metode pengembangan R&D dengan model pengembangan luther-sutopo. Metode pengumpulan data yaitu survey. Instrumen penelitian yaitu lembar validasi. Teknik analisis data dengan mendeskripsikan tahapan pengembangan media web dengan model pengembangan luther-sutopo. Hasil analisis data menunjukkan tingkat kelayakan dari ahli materi sebesar 76,66% (kategori layak), ahli media sebesar 100% (sangat layak). Pada tahap uji coba beta didapatkan sebesar 95,33% termasuk kategori sangat layak. This study aims to develop web-based learning media based on junior high school students' behaviorism in honing mathematical numeracy skills and to test the feasibility of learning media. Using the R&D development method with the Luther-Sutopo development model. The data collection method is a survey. The research instrument is a validation sheet. Data analysis techniques by describing the stages of web media development with the Luther-Sutopo development model. The results of the data analysis show the level of feasibility from material experts of 76.66% (feasible category), and media experts of 100% (very possible). At the beta trial stage, 95.33% were obtained, including the very feasible category.